RAGAM BAHASA PADA JEJARING SOSIAL FACEBOOK DAN PENGGUNAANNYA SEBAGAI ALTERNATIF BAHAN PEMBELAJARAN BAHASA INDONESIA - Saroh Saroh; Dase Erwin Juansah (Universitas Sultan Ageng Tirtayasa, 2018)
As the most preferred social networking, facebook also become the most prolific media examples to show the language used in the community in various ways. Language varieties that appear extremely varied, ranging from formal language to more familiar one. Variety of language is language variations or demands to use different language styles depending on places, topics, speakers, medium, and so on. The purpose of this study was to determine the suitability of language varieties in students’ facebook status of SMA Negeri 1 Cipanas Lebak year 2016/2017 with teaching materials selection criteria in order to use it in teaching Indonesian for senior high school. This is a qualitative research with content analyze technique. The method used in this study was observation with the tapping technique. In addition, this study used data collection method in the form of literature studies and interviews. In this study 100 data were taken and classified into language varieties. The result showed the type of language varieties in the form of (1) a variety of language, kronolek, (2) Colloquial, (3) ken, (4) slang, (5) jargon, (6) familiar, (7) formal, and (8) casual. Based on the analysis of the selection criteria for instructional materials reinforced by interviews and questionnaires, facebook status can be used as an alternative material language learning material in editing errors and identifying standard and non-standard language, so that learning can be more interesting and fun.